Karakterisasi Arang Karbon Hasil Pirolisis Limbah Kulit Pinang Dengan Dan Tanpa Ethanol Sebagai Aktivator - Peday, Harold Thijs Nadyo; Sialana, Jufri; Mini, Marthina; Nanlohy, Hendry Y (Fakultas Teknik UMSU, 2025)
Activated carbon is a crucial material widely used in various applications, including water purification and waste treatment. Areca nut husk, often regarded as waste, shows great potential as an alternative raw material for activated carbon. This study aims to characterize the structure and chemical properties of activated carbon derived from areca husk waste through an ethanol activation process. The activation process was conducted to enhance the porosity and surface area of the activated carbon, thereby increasing its adsorption capacity. Microstructure observations, XRD, TGA, and FTIR analyses were conducted to evaluate the quality of the activated carbon. The results showed that activated carbon with activation has a more complex pore structure, higher crystallinity, and additional functional group such as hydroxyl, which improve adsorption capacity and thermal stability. This study demonstrates that ethanol-activated areca husk has significant potential for various environmental and industrial applications.